Предмет: Математика,
автор: Valeriya9438
Упростите примеры
a-5p-5a+3p=
-(2a-p)-3(a+2p)=
4y-3-2(5-y)=
3x-1-(-2x+(1+3x))
Ответы
Автор ответа:
0
а-5р-5а+3р=а-5а-5р+3р=а(1-5)-р(3-5)=-4а+2р
-(2а-р)-3(а+2р)= -2а+р-3а-6р=-5а-5р=-5(а+р)
4у-3-2(5-у)=4у-3-10+2у=6у-13
3х-1-(-2х+(1+3х))=3х-1-(-2х+1+3х)=3х-1+2х-1-3х=2х-2
Автор ответа:
0
Спасибо
Похожие вопросы
Предмет: Алгебра,
автор: GmGrims
Предмет: География,
автор: gluskouliana13
Предмет: Математика,
автор: bnikolaev529
Предмет: Математика,
автор: zkaynarov
Предмет: Физика,
автор: oooblezov